Analisis Struktur Kepribadian Tokoh Afa Dalam Novel El Verano Karya Pia Devina - Naufal Indrafara; Annanda Hariz; Eva Dwi Kurniawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Abstract: The aim of this research is to apply analysis of Sigmund Freud's theory, namely personality structure, namely Ideas, Ego, Super Ego to literary works. The work is based on the novel genre with the title El Verano by Pia Devina. This research uses a literary psychology approach with reading and analyzing analysis techniques. This research method is qualitative, based on Sigmund Freud's psychoanalytic theory. The results obtained show that the idea of ​​the character Afa has a strong id, seen from the many id impulses that appear in him, such as impulses to act aggressively, avoid responsibility, attack others, express emotions directly, and avoid fear. The ego of Afa's character is quite good, seen from his ability to control his id impulses, express his emotions naturally, make realistic decisions, understand other people's feelings, build relationships with other people, and achieve satisfaction. Super Ego The character Afa has a developed superego, which can be seen from his ability to feel various kinds of moral emotions, such as feelings of guilt, regret, shame, wanting to be a better person, wanting to forgive, wanting to be a strong person, and feelings of satisfaction.